Metabolism Reactivation in Erythrocytes Cryopreserved with Polyethylene Glycol: Protein State and Reactive Oxygen Species Production - Zemlianskykh, Nina; Babijchuk, Lyubov (Problems of Cryobiology and Cryomedicine, 2022)
Production of reactive oxygen species (ROS) and protein state of membrane-cytoskeleton complex (MCC) in the erythrocytes, subjected to freeze-thawing with polyethylene glycol (PEG) and subsequently transferred into physiological conditions in vitro after cryoprotective agent removal were examined. Results of SDS-PAGE with β-mercaptoethanol showed a decrease in spectrin content in the MCC profile of cryopreserved erythrocytes. The using of diamide revealed an increase in the accessibility of –SH groups of spectrin for the reagent and an enhanced level of high molecular weight polypeptide complexes relative to the control. A decrease in the content of protein band 8 (peroxiredoxin) in the MCC of cryopreserved erythrocytes revealed by SDS-PAGE with β-mercaptoethanol is apparently associated with a change in its localization caused by an increased ROS production at the previous stages of cryopreservation. At the same time, the absence of significant changes in the ROS production relative to the control upon the metabolism reactivation in erythrocytes indicated the ability of cryopreserved cells to control the oxidative processes during short-term incubation. Probl Cryobiol Cryomed 2022; 32(2):092–103